Revolusi Mental Bidang Pendidikan Pada Masyarakat Ekonomi ASEAN (MEA) - Widhiya Ninsiana (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
Asean Economic Community (AEC) is a free market at the level of the countries of Southeast Asia. Free competition in afree market of AEC consists of 12 sectors, namely the 5 sectors of industry service, and 7 sectors in trade and industries. One of the strategic effort to develop competitiveness in the AEC is doing strategic efforts in optimizing education. Strategic efforts in education needs to be done, such as improvements in the areas of education, teachers and curriculum. Mental revolution in the field of education is one of the president’s Jokowi agenda. Mental revolution in education in line AEC program, namely strengthening the field of education, the education of character. The formation of character as well and gives meaning to the improvement of the quality of students’ academic skills, improving the quality of the curriculum, the quality of schools and education.